Fungal endophytes of Brassicaceae: Molecular interactions and crop benefits - Poveda, Jorge; Díaz-González, Sandra; Díaz-Urbano, María; Velasco, Pablo; Sacristán, Soledad (Frontiers in Plant Science, 2022)
Brassicaceae family includes an important group of plants of great scientific interest, e.g., the model plant Arabidopsis thaliana, and economic interest, such as crops of the genus Brassica (B. oleracea, B. napus, B. rapa, etc.). This group of plants is characterized by the synthesis and accumulation in their tissues of secondary metabolites called glucosinolates (GSLs), sulfur-containing compounds mainly involved in plant defense against pathogens and pests. Brassicaceae plants are among the 30% of plant species that cannot establish optimal associations with mycorrhizal hosts (together with other plant families such as Proteaceae, Chenopodicaceae and Carophyllaceae), and GSLs could be involved in this evolutionary process of non-interaction. However, this group of plants can establish beneficial interactions with endophytic fungi, which requires a reduction of defensive responses by the host plant and/or an evasion, tolerance or suppression of plant defenses by the fungus. Although much remains to be known about the mechanisms involved in the Brassicaceae-endophyte fungal interaction, several cases have been described in which the fungi need to interfere with the GSL synthesis and hydrolysis in the host plant, or even directly degrade GSLs before they are hydrolyzed to antifungal isothiocyanates. Once the Brassicaceae-endophyte fungus symbiosis is formed, the host plant can obtain important benefits from an agricultural point of view, such as plant growth promotion and increase in yield and quality, increased tolerance to abiotic stresses, and direct and indirect control of plant pests and diseases. This review compiles studies on the interaction between endophytic fungi and Brassicaceae plants, discussing the mechanisms involved in the success of the symbiosis, together with the benefits obtained by these plants. Due to their unique characteristics, the family Brassicaceae can be seen as a fruitful source of novel beneficial endophytes with applications to crops, but also to generate new models of study that allow us to better understand the interactions of these amazing fungi with plants.